Boosting the photocatalytic activity of electrolyte for higher energy efficiency in water electrolysis under influence of an optimal laser. Issue 1 (1st December 2022) - Niaz, U; Aziz, M S; Mufti, N; Salleh, M S; Krishnan, G; Daud, S; Abdullah, Faizuan; Wirzal, M D H
Abstract: In current study a careful and dedicated observation was done to investigate the effect of the externally applied optical field on electrolysis of water to produce hydrogen. As optical field sources, the green and red diode pumped solid state lasers (DPSSL) were utilized. Due to its non-absorbance characteristics in water, the green laser has had the largest impact on the generation/production of hydrogen. In order to dissociate hydronium and hydroxide ions during orientation toward polarisation of water, the electrical field's intensity must be high enough. The mechanism of optical field to expose the hydrogen production in water electrolysis has the capability to break the autoprotolysis and generate the auto-ionization. However, the presence of a sacrificial agent and a laser source combined to produce a better effect, resulting in a five-fold increase in hydrogen output compared to ordinary water electrolysis. UV-Vis and the gas chromatography was performed for supporting the research claim. The gas chromatogram was indicating a clear peak at retention time 1.47 minutes with abundance 338878 a.u. which predicts the purity and abundance of produced hydrogen.